Fraid E. Cat - Newman, Al.; Doody, Jim (Milwaukee, Wis. : Gareth Stevens Pub., 1995)
This friendly and playful cat needs to learn that there really are no scary monsters in her room and that she just imagines they are around her at night.
"First published in 1993 by Humanics Children$1 (Bs House".s
Keywords: Cats -- Fiction; Imagination -- Fiction; Fear -- Fiction; Stories in rhyme